A new species of Amphinemura (Plecoptera: Nemouridae) from Guangxi Zhuang Autonomous Region of southern China - Mo, Raorao; Wang, Guoquan; Yang, Ding; Li, Weihai (Zootaxa, 2019)
A new species of the Amphinemurinae genus Amphinemura, A. baisensis sp. nov. is described from Guangxi Zhuang Autonomous Region of southern China. Affinities of the new taxon with similar regional species of Amphinemura are discussed.